Belief in god and altruism. Is there any effect? - Kuzenbayev, Nygmetzhan (Nazarbayev University School of Sciences and Humanities, 2018)
The influence of individual’s belief in God and other factors, such as religiousity, education, perception of happiness, et cetera, on altruistic behavior was empirically examined during this study. It was discovered that “it is important to do something for the good of society” to people that believe in God. However, belief in God decreases the probability of participation in humanitarian and charitable organizations.
Keywords: altruism, charity, God, religiousity